2002
DOI: 10.1111/j.1365-2508.2002.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intrauterine disorders by hysteroscopy and transvaginal sonography

Abstract: Objective  To compare the diagnostic accuracy of transvaginal sonography and hysteroscopy for intrauterine disorders. Design  300 patients were investigated by transvaginal sonography for abnormal vaginal bleeding. Of these, 112 had subsequent hysteroscopic examination and then had concomitant surgery. Results  The accuracy of findings at hysteroscopy and transvaginal ultrasonography were compared with the histopathological and surgical results as the gold standard diagnosis. The sensitivity, specificity, posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Only in the range between 0.07% and 0.6% are patients asymptomatic. [3][4][5] In about 10% of cases AUB is associated with endometrial cancer, but it can be caused by many other conditions, such as polyps, myomas, hormonal dysfunction and, most commonly in postmenopausal women, atrophy. 6,7 Endometrial pathology can be identified using several methods, such as transvaginal ultrasound with or without Color-Doppler and 3-D analysis, hysteroscopy and endometrial biopsy, sonohysterography and the presence of endometrial cells in cervical cytology slides.…”
Section: Introductionmentioning
confidence: 99%
“…Only in the range between 0.07% and 0.6% are patients asymptomatic. [3][4][5] In about 10% of cases AUB is associated with endometrial cancer, but it can be caused by many other conditions, such as polyps, myomas, hormonal dysfunction and, most commonly in postmenopausal women, atrophy. 6,7 Endometrial pathology can be identified using several methods, such as transvaginal ultrasound with or without Color-Doppler and 3-D analysis, hysteroscopy and endometrial biopsy, sonohysterography and the presence of endometrial cells in cervical cytology slides.…”
Section: Introductionmentioning
confidence: 99%
“…Transvaginal ultrasound fails to differentiate intrauterine abnormalities (i.e., myomas, polyps, hyperplasia, etc. ), so having a low diagnostic sensitivity ranging from 76% to 96% [4,5]. Visualization of the endometrial echo or endomyometrial complex may also be limited by the uterine position, myometrial lesions that distort endometrial line, and by the resolution of the imaging technology.…”
Section: Discussionmentioning
confidence: 99%
“…Their incidence varies depending upon the population under study and can range between 7.8-34.9%. 6,7 Intrauterine pathologies are diagnosed by transvaginal ultrasound as a first line investigation. However, its sensitivity ranges between 76% to 96%.…”
Section: Discussionmentioning
confidence: 99%